METABOLICALLY ASSOCIATED FATTY LIVER DISEASE IN PATIENTS WITH VERY HIGH CARDIOVASCULAR RISK: PREVALENCE, CLINICAL SIGNIFICANCE, GENDER DIFFERENCES - Koroliuk, Olha; Komarytsia, Orest; Huk-Leshnevska, Zoriana; Zenin, Vadym (Eastern Ukrainian Medical Journal, 2024)
Introduction. Recently, metabolically associated fatty liver disease (MAFLD) had been proposed as a new term. Due to increasing prevalence, significant morbidity and hepatic and cardiovascular mortality, the association of MAFLD with cardiovascular diseases is gaining considerable relevance and needs further study. The aim of our study was to determine the proportion of MAFLD among patients with a very high cardiovascular risk, and to elucidate clinical features and gender differences in this cohort.Materials and methods. All patients underwent a comprehensive examination to assess both cardiovascular risk and MAFLD. Hepatic steatosis was diagnosed after liver ultrasonography. Participants who met MAFLD criteria were included into the group 1 (n=77; 32 women, 45 men), other patients were assigned to the group 2 (n=39; 19 women, 20 men).Results. Among patients with very high cardiovascular risk, proportion of MAFLD was 66.7 %. Although mild alanine aminotransferase elevation was much more common among patients with MAFLD (16 women (50.0 %) vs. 2 women (10.5 %) in group 2, P = 0.006; 21 men (46.7 %) vs. 2 men in group 2 (10.0 %), P = 0.005), none of the participants met the criteria for steatohepatitis. Despite, the presence of metabolic disorders in the vast majority of participants, proportion of obesity, metabolic dyslipidaemia, prediabetes and type 2 diabetes were significantly higher in patients with MAFLD. Besides, patients with MAFLD usually met 4 or 5 metabolic syndrome criteria, had higher median values of lipid accumulation product (LAP) and HOMA-IR index, but lower median values of Matsuda index. Significant direct correlations were found between MAFLD and LAP, logarithmic index (TG/HDL-C), and HOMA-IR; negative correlations were observed between MAFLD and insulin sensitivity indices. Women with MAFLD had significantly higher median values of glycated haemoglobin, post-load glucose, fasting insulin levels; there was direct correlation between MAFLD and non-HDL-C. Among women with MAFLD, a history of menopause before 45 years of age had 15 persons (46.9 %) vs. one person (5.3 %) in group 2 (P < 0.002); the median age when ASCVD was diagnosed was 58.5 [53.0; 64.0] years vs. 68.0 [63.0; 69.0] years in group 2 (P = 0.002); cardiac valve calcinosis was detected in 31 women (96.6 %) vs. 9 women (47.4 %) in group 2 (P = 0.0001); the left ventricular myocardial mass (LVM) index was 77.5 [62.1; 86.9] g/m2.7 vs. 64.0 [50.6; 74.0] g/m2.7 in women without MAFLD, 67.0 [55.1; 74.0] g/m2.7 in men with MAFLD, and 63.9 [50.0; 73.5] g/m2.7 in men without MAFLD (Kruskal–Wallis ANOVA P <0.0001; median test P=0.002). The prevalence of smoking and alcohol intake was significantly more common among men (gender differences P <0.0001 and P=0.0001 in group 1; P = 0.0004 and P=0.0023 in group 2 for smoking and alcohol intake, respectively). Men with MAFLD had significantly higher median values of fasting plasma glucose, fasting and post-load insulin levels than men without MAFLD; there was a significant direct correlation between MAFLD and serum TG level. In addition, 11 men with MAFLD (24.4 %) had hypertriglyceridemia >2.3 mmol/l that was not observed among men without MAFLD (P=0.013). The proportion of men with fasting and post-load hyperinsulinemia was much higher in group 1 than in group 2 (28 persons (62.2%) vs. 3 persons (15.0 %), P=0.0005 and 26 persons (57.8%) vs. 2 persons (10.0 %), P = 0.0003, respectively).Conclusions: among patients with a very high cardiovascular risk, the prevalence of MAFLD was significantly higher than in the general population. Concomitant MAFLD was associated with more severe metabolic disorders (i.e., obesity, metabolic dyslipidaemia, hyperglycaemia, insulin resistance), which usually combined. The LAP index is a simple available tool that may be used in routine clinical practice to determine the need for MAFLD screening. Women with MAFLD frequently had early menopause, cardiac valve calcification, and much higher median value of LVM index; direct correlation was observed between MAFLD and non-HDL-C. Men with MAFLD more often had fasting and/or post-load hyperinsulinemia and moderate hypertriglyceridemia